Proses Pemberdayaan Masyarakat Melalui Budidaya Lidah Buaya di Kelurahan Kebon Pala Jakarta Timur - Dari Annastasya; Isna Rahmawati (Empower : Jurnal Pengembangan Masyarakat Islam, 2022)
Pokja III PKK Kebon Pala empowering the community through aloe vera cultivation. This activity is hold to utilize the yard around their houses. This study aims to determine the process and the impact of community empowerment through aloe vera cultivation that was pioneered by Pokja III PKK Kebon Pala. This study uses qualitative approach supported by descriptive analysis, data was obtained from observations and interviews. Data analysis through reducing, presenting, verivication and conclution. The result shows that community empowerment that was pioneered by Pokja III PKK Kebon Pala can be seen through awareness, capacity increase and empowerment. Community empowement process by Pokja III PKK Kebon Pala successfully empowering the community because it improves knowledge and skill through aloe vera cultivation, increase community’s income, keep environment clean and safe, and stregthening the institution of PKK.